Perlindungan Hukum Bagi Pekerja Pada Perusahaan Outsourcing Dengan Status Perjanjian Kerja Waktu Tertentu Yang Dipekerjakan Pada Pekerjaan Inti Perusahaan - Endry Loman; Andari Yurikosari (Fakultas Hukum Universitas Tarumanagara, 2020)
This Paper is based on a study of the cassation verdict number 712/K/Pdt.Sus-PHI/2018 which canceled the decision of the district court at the previous level. This study aims to learn how to distinguish between the company’s core business and supporting business. It is done to achieve legal certainty, especially outsourcing so that the workers and companies are not disadvantaged. Besides, to find out where the application of the employment agreement is intended specifically for permanent jobs. In reality, the relationship between workers and employers is not by the words of the law. We cannot deny that the practice of outsourcing cannot be eliminated. During intense business competition and the advancement of the business world, no company can survive without outsourcing. In practice, outsourcing is considered a modern slavery, but on the other hand, outsourcing cannot be eliminated. The question arises, is our positive law, namely law number 13 of 2003, the ruling of the constitutional court number 27/PUU-IX/2011 and related ministerial regulations sufficient to protect workers as well as beneficial employers? Therefore, the most important things is to do law enforcement related to outsourcing and monitoring of the outsourcing practices to respond to the times without harming any parties.